Analisis Faktor-Faktor yang Mempengaruhi Rendahnya Pembiayaan Mudharabah Menurut Perspektif Manajemen Bank Syariah dengan Pendekatan Kritis - Adnan, Muhammad Akhyar; Purwoko, Didi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2013)
Ths study is trying to identify the factors behind the low volume of mudharabah contracts agreed or signed by the Isamic banks generally as compared to Murabaha. Three BPRS (Bank Pembiayaan Rakyat Syariah – Rural Syariah Banks) in Yogyakarta have been chosen to be studied. These include BPRS Bangun Drajat Warga (BDW), Barokah Dana Sejahtera (BDS) dan Amal Mulia. The qualitative and critical approaches have been applied in this study. Some important key persons in each bank have been interviewed deeply. They include the members of Dewan Pengawas Syariah (Shariah Supervisory Board), Top management until middle management level. There are eleven factors identified to have an influence on the low portion of mudharabah released by the syariah banks. These include (among others) the risk, uncertainty, report mechanism, high NPF, difficulty in analysis, partner’s tranparency, human resource capacity, lack of trust.